1996
DOI: 10.1038/bjc.1996.57
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between integrin alpha 5 expression and the malignant phenotype of transitional cell carcinoma

Abstract: Summary We examined the expression of al, a2, a3, a4, a5 and ,B1 integrin on 36 transitional cell cancers (TCCs) in the bladder by immunohistochemistry. Only a2, a3 and /31 were detected on normal transitional cell epithelium, but four TCCs (12.5%) revealed positive staining for al, seven (19.4%) for a4 and seven (20%) for a5. These altered expressions of integrin a chain were more frequent in histologically higher stage or grade of TCC, and a correlation was found between increased aS expression and histolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 20 publications
3
21
1
Order By: Relevance
“…In non-small lung carcinoma cells, higher levels of a5b1 expression represents a negative prognostic factor (Adachi et al, 2000). Similar results have also been shown with other human tissues that high levels of a5b1 integrin is associated with more malignant phenotype in melanoma, transitional and colon cell carcinomas (Saito et al, 1996;Gong et al, 1997;Beliveau et al, 2000). The a5b1 integrin favours cell survival and protects cells from apoptosis in vitro via upregulation of anti-apoptotic Bcl-2, whereas resistance to apoptosis is a feature of many malignant cells (Zhang et al, 1995).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In non-small lung carcinoma cells, higher levels of a5b1 expression represents a negative prognostic factor (Adachi et al, 2000). Similar results have also been shown with other human tissues that high levels of a5b1 integrin is associated with more malignant phenotype in melanoma, transitional and colon cell carcinomas (Saito et al, 1996;Gong et al, 1997;Beliveau et al, 2000). The a5b1 integrin favours cell survival and protects cells from apoptosis in vitro via upregulation of anti-apoptotic Bcl-2, whereas resistance to apoptosis is a feature of many malignant cells (Zhang et al, 1995).…”
Section: Discussionsupporting
confidence: 78%
“…There is evidence that osteosarcoma cells that overexpress integrin a5b1 show reduced invasive potential (Giancotti and Ruoslahti, 1990). In contrast, upregulation of a5b1 has been shown to correlate with invasive phenotype in colon cancer and transitional cell carcinoma (Saito et al, 1996;Gong et al, 1997). Similarly, recent data show that high levels of integrin a6 in breast cancer and avb3 in melanoma correlate with tumour progression (Mukhopadhyay et al, 1999;Hofmann et al, 2000).…”
mentioning
confidence: 99%
“…It was reported that integrin α5 contributes to a more malignant phenotype in urothelial bladder cancer (22). In our study, this integrin subunit was overexpressed in most of the tested chemoresistant sublines what might underline the more malignant phenotype of the chemoresistant sublines (Fig.…”
Section: Discussionmentioning
confidence: 56%
“…However, our results agree with those reported by other authors that have found comparable levels of α 5 and β 1 integrins in transformed human bronchial epithelial cells [34]and in different CT-26 colon carcinoma sublines showing different tumorigenic capacity [29]. In addition, it has been described that the expression of α 5 -integrin might be correlated with a more malignant phenotype [13, 14, 15, 35]. In our system, the cell surface levels of α 5 β 1 do not seem to be related with the tumorigenic potential.…”
Section: Discussioncontrasting
confidence: 45%
“…Several reports have suggested that the expression levels of α 5 β 1 integrin inversely correlate with malignancy [9, 10, 11, 12]. However, a decrease in α 5 β 1 expression does not always parallel an increase in the malignant potential of carcinoma cells: (1) in transitional cell carcinoma, a direct correlation between α 5 β 1 integrin expression and a more malignant phenotype has been described [13]; (2) genetic studies in mice have shown that the loss of FN or α 5 β 1 integrin does not contribute to tumorigenesis [14]; (3) the overexpression of this integrin has been proposed as a significant predictive factor for a poor prognosis in node-negative patients with non-small-cell lung cancer [15]. In colon cancer cells, α 5 β 1 is either not expressed at all [16], or only poorly expressed compared to normal epithelial cells [7]; contradictory data regarding the expression of this integrin in HT 29 cells have been reported [10, 16].…”
Section: Introductionmentioning
confidence: 99%